Knowledge toward epilepsy among Ardabil Medical University students: North-West of Iran - Abbasi, Vahid; Atalou, Abolfazl; Amani, Firouz; Fezollahzadeh, Hadi (International Journal of Contemporary Pediatrics, 2018)
Background: Medical university students is a better group of society that should be had correct and good knowledge about healthcare issues such as epilepsy. Epilepsy is a common neurologic disease that caused to many problems in patient’s life. This study aimed to evaluate the knowledge of medical students toward epilepsy in Ardabil province. Methods: A cross-sectional descriptive survey was conducted in Ardabil province (Northwest of Iran) in 2017. Over a one-month period, 130 students selected randomly from all medical, paramedical, nursing and health students and completed the self-administered questionnaire which provided for this study. Collected data analyzed by statistical methods in SPSS version 19. Results: Of all students, 83.1% were girls and rests of them were boy. Of all students 20% had good and 56.2% had moderate knowledge about epilepsy. Many of students in all fields had moderate knowledge and there wasn’t significant relation between field, semester and knowledge rate. Most of boys with 54.5% had week and most of girls with 58.3% had moderate knowledge and there was significant relation between sex and knowledge rate. Conclusions: Results showed that most of students in this study had moderate knowledge about epilepsy. Students had poor knowledge about important point about diseases such as treatment, diagnosis. Providing necessary training programs for knowing this disease in future for students is essential.